Docosahexaenoic acid causes rapid pulmonary arterial relaxation via KCa channel-mediated hyperpolarisation in pulmonary hypertension. Issue 4 (18th August 2016) - Nagaraj, Chandran; Tang, Bi; Nagy, Bence M.; Papp, Rita; Jain, Pritesh P.; Marsh, Leigh M.; Meredith, Andrea L.; Ghanim, Bahil; Klepetko, Walter; Kwapiszewska, Grazyna; Weir, E. Kenneth; Olschewski, Horst; et al.
Cardioprotective benefits of ω-3 fatty acids such as docosahexaenoic acid (DHA) are well established, but the regulatory effect of DHA on vascular tone and pressure in pulmonary hypertension is largely unknown. As DHA is a potent regulator of K + channels, we hypothesised that DHA modulates the membrane potential of pulmonary artery smooth muscle cells (PASMCs) through K + channels and thus exerts its effects on pulmonary vascular tone and pressure. We show that DHA caused dose-dependent activation of the calcium-activated K + (KCa) current in primary human PASMCs and endothelium-dependent relaxation of pulmonary arteries. This vasodilation was significantly diminished in KCa –/– (Kcnma1 –/– ) mice. In vivo, acute DHA returned the right ventricular systolic pressure in the chronic hypoxia-induced pulmonary hypertension animal model to the level of normoxic animals. Interestingly, in idiopathic pulmonary arterial hypertension the KCa channels and their subunits were upregulated. DHA activated KCa channels in these human PASMCs and hyperpolarised the membrane potential of the idiopathic pulmonary arterial hypertension PASMCs to that of the PASMCs from healthy donors. Our findings indicate that DHA activates PASMC KCa channels leading to vasorelaxation in pulmonary hypertension. This effect might provide a molecular explanation for the previously undescribed role of DHA as an acute vasodilator in pulmonary hypertension. Increased KCa channels in remodelled pulmonary artery of IPAH might be a therapeutic opportunity for DHA http://ow.ly/rTUl300pn7R